2020
DOI: 10.3390/ijms21238966
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Activation Protects Ocular Surface from Inflammation in a Dry Eye Model In Vitro

Abstract: Inflammation is the main pathophysiology of dry eye, characterized by tear film instability and hyperosmolarity. The aim of this study was to investigate the association of inflammation and cellular autophagy using an in vitro dry eye model with primary cultured human corneal epithelial cells (HCECs). Primary HCECs cultured with fresh limbal explants from donors were switched to a hyperosmotic medium (450 mOsM) by adding sodium chloride into the culture medium. We observed the stimulated inflammatory mediators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…The study of tear osmotic pressure and dry eye severity showed that with the aggravation of dry eye, tear osmotic pressure increased significantly. This was consistent with the research results of Liu et al (2020) [19]. Additionally, van Setten (2019) [20] proposed that different osmotic pressures may be the key mechanism leading to cell death, inflammation, apoptosis, and goblet cell loss observed in dry eye.…”
Section: Discussionsupporting
confidence: 91%
“…The study of tear osmotic pressure and dry eye severity showed that with the aggravation of dry eye, tear osmotic pressure increased significantly. This was consistent with the research results of Liu et al (2020) [19]. Additionally, van Setten (2019) [20] proposed that different osmotic pressures may be the key mechanism leading to cell death, inflammation, apoptosis, and goblet cell loss observed in dry eye.…”
Section: Discussionsupporting
confidence: 91%
“…In DED, some established in vitro models have also been established: the Wong Kilbourne derivative of Chang conjunctival epithelial cell line (WKD; clone 1-5c-4) [47][48][49][50][51]; immortalized normal human conjunctival cell line (IOBA-NHC) [47,52,53]; human corneal epithelial cells (HCECs), a human transformed SV40 immortalized corneal epithelial cell line [54,55], and human conjunctival cell line (HCC) [56]. In vitro models with primary cell culture are also available: human corneal epithelial cells (HCECs) [57], rabbit corneal epithelial cells (CECs), or rabbit LG acinar cells (LGACs) [58]. The induction of DED-like symptoms in in vitro culture can be performed by the induction of hyperosmotic (500 mOsM) media in the culture media by the addition of 90 mM sodium chloride in the culture medium, which triggers inflammatory-like symptoms [47,48,55,57,59].…”
Section: In Vitro Dry Eye Modelmentioning
confidence: 99%
“…In vitro models with primary cell culture are also available: human corneal epithelial cells (HCECs) [57], rabbit corneal epithelial cells (CECs), or rabbit LG acinar cells (LGACs) [58]. The induction of DED-like symptoms in in vitro culture can be performed by the induction of hyperosmotic (500 mOsM) media in the culture media by the addition of 90 mM sodium chloride in the culture medium, which triggers inflammatory-like symptoms [47,48,55,57,59]. As in the in vivo experiment, benzalkonium chloride (BAC) (0.0001% (1 µg/mL) was also used to induce inflammatory cascades [47][48][49][50][51][52].…”
Section: In Vitro Dry Eye Modelmentioning
confidence: 99%
“…Liu Zhao et al founded that autophagy activation is a late response of HcECs to hyperosmotic stress after inflammation is triggered, which protects HcECs and promotes survival by reducing inflammatory mediators in an vitro model of dry eye. These protective effects were further enhanced when rapamycin enhanced autophagy activation in hypertonic HCECs (Liu et al, 2020a). In addition, they suggest that trehalose, as an autophagy enhancer, induces autophagy antiinflammation by inhibiting Akt activation of transcription factor EB in primary HCECs exposed to high osmotic stress (Liu et al, 2020b).…”
Section: Autophagy and Inflammationmentioning
confidence: 87%